Experience of Peace Activates in Sri Lanka - Dhammajothi, M. (My University, 2008)
Peace building, though the phrase sounds very simple, is definitely a ‘complex task of great magnitude. Therefore, it should be undertaken with the seriousness it demands and deserves. Sporadic and unorganized attempt at peace building, I feel, will create more punctures, some of which may even cause irreparable damage. Hence, it should be carried out according to a well planned, methodically phased out programme. For this there should be extremely committed, truly dedicated person as well as institutions, who can work, putting aside personal agendas, whatever form these agendas may take, and also who can rise about petty divisive forces. Experience shows that what is of primary importance is building of trust and confidence of all parties affected by breach of peace. Without fulfilling this primary requirement no peace building effort will be able to achieve the objectives envisaged. Peace building is necessitated by the fact of peace being breached. Therefore, as an initial step it is necessary to identify correctly the factors that contributed, in different measures, to this breaching of peace. These factors may be economic, ideological political social, cultural etc. These have to be identified by those who venture at peace building, and try to avoid involving whatever factors –whether individuals or institution, attempting to surreptitiously promote any of the above referred to divisive forces. It is only then that parties affected will begin to repose confidence, trust and faith in the peace building process and the people and institutions involved in such a process.